Workshop Software Bidang Teknologi Informasi di Era Revolusi Industri 4.0 di SMK Negeri 1 Kutalimbaru Kabupaten Deliserdang - Burhanuddin Damanik; Riah Ukur Ginting; Dini Maria Hutagalung; Hestina Hestina Hestina; Maniur Arianto Siahaan (Universitas Medan Area, 2020)
Along the industry revolution 4.0 progress, there are many applications created to help people to do their jobs. Suc as registration online application to continue their study in university, applying jobs, and employment registration. The most popular files format today that people commonly use are *.jpeg and 8.pdf. Because many registration or administration filing digital management use these kind of soft files. Therefore, System Information Program of Sari Mutiara Indonesia University went to schools to do community service to teach students to do Workshop in SMK Negeri 1 Kutalimbaru Kabupaten Deliserdang. The workshop materials are : Nitro Software Installation, Tutorial and Practical with Ntrio 10 and Microsoft Picture Manager. The goals of the Community Service is to train the students to know how to convert any Office Applications documents format into *.pdf format, manipulate or change the size of an image or picture and how to put it in one documents.